To evaluate the analgesic efficacy of intravenous dexamethasone as an adjuvant to caudal block: A prospective, randomized, double-blind study - Neetu Gupta,; Yogesh Dodiyar,; Khushal Bokde,; Sharma, Aseem; K.K. Arora, (Asian Journal of Medical Sciences, 2023)
Background: Post-operative pain is of great concern in pediatric age group. Intravenous dexamethasone has been found to be promising in reducing post-operative pain when administered as an adjuvant to epidural anaesthesia in abdominal and orthopedic surgeries. However, little is known about its efficacy in children receiving caudal block for post-operative pain relief. Aims and Objectives: This study aimed to evaluate the analgesic efficacy of intravenous dexamethasone as an adjuvant to caudal block in children posted for infraumbilical surgeries. Materials and Methods: This interventional, double-blinded, randomized controlled study included 110 children aged 1–5 years with American Society of Anesthesiologists Grade I and II undergoing elective infraumbilical surgeries. To test our hypothesis, the superiority of intravenous dexamethasone was compared with the control group. All children received caudal bupivacaine 0.25% (1 mL/kg). Children were randomly allocated to two groups to receive: normal saline 0.075 mL/kg (Group C) and IV dexamethasone 0.3 mg/kg (0.075 mL/kg) (Group D). Post-operative pain scores (Face, Legs, Activity, Cry, and Consolability [FLACC] score), duration of analgesia, post-operative analgesic consumption, and intraoperative hemodynamics were compared. Results: FLACC score was found to be higher in Group C than Group D at all times. The mean FLACC score was significantly less with the study drug compared to the control group (P<0.001). The time to request for first rescue analgesia was significantly less in Group C as compared to Group D (4.01±0.69 h vs. 5.51±0.50 h, P=0.019). The mean total analgesic consumed in the first 24 h was significantly higher in Group C than in Group D (666.09±174.69 mg vs. 384.55±125.04 mg, P=0.015). Hemodynamic parameters were comparable in both the groups. Conclusion: Intravenous administration of dexamethasone 0.3 mg/kg as an adjunct to caudal bupivacaine 0.25% provides significantly longer duration of post-operative analgesia and lesser total analgesic consumption compared to the use of caudal bupivacaine 0.25% alone.